Factors Influencing the Effectiveness of Budgeting in Manufacturing Companies: A Systematic Review of the Literature (SLR) - Khalifa, Savana Putri; Hermawati, Novi; Fitri, Cut Elisa; Zahra, Nashwa Fachira; Abro, Najwa Apriyanda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the factors influencing the effectiveness of budget allocation in manufacturing companies using a Systematic Literature Review (SLR) approach. The SLR method is employed to systematically examine relevant scientific articles published in both national and international journals. Articles were selected based on specific inclusion criteria, focusing on budgeting, budget effectiveness, and the manufacturing industry context. The results of the review indicate that budget effectiveness is shaped by a combination of internal and external factors. Internal factors include managerial participation in the budgeting process, the quality of financial information systems, human resource competencies, cross-functional coordination, and the strength of internal control mechanisms. Active involvement of managers enhances budget accuracy and commitment, while reliable information systems and competent personnel support better planning and monitoring. Effective coordination among departments and strong internal controls further ensure that budgets are implemented as intended. External factors also play a significant role in determining budgeting effectiveness. These factors include macroeconomic conditions such as inflation, fluctuations in raw material prices, exchange rate volatility, government regulations, and rapid developments in information technology. Such external dynamics can create uncertainty and risk, requiring companies to adapt their budgeting processes accordingly. The interaction between internal and external factors ultimately determines the extent to which budgets function effectively as tools for planning, control, and decision-making. Therefore, manufacturing companies need to strengthen internal capabilities while remaining responsive to changes in the external environment.